Penta-Helix Model of Merdeka Kurikulum to Address Learning Loss at SMA Al-Islam 1 Surakarta - Mustofa, Rochman Hadi; Ramadhan, Muhammad Tanzilal; Buana, Dewangga Satria; Karima, Mutiara; Narmanditya, Bagus Shandy (Proceedings International Conference on Education Innovation and Social Science, 2024)
The learning loss that emerged after online learning during the COVID-19 pandemic has resulted in low motivation and slow psychological development among students. This study aims to investigate the implementation of strategies to address learning loss through the implementation of the Merdeka Curriculum at SMA Al-Islam 1 Surakarta, a "Sekolah Penggerak" (Catalyst School) in Indonesia. This study employs a qualitative case study design, collecting data through interviews, documentation, and observation. The results reveal that the implementation of the Merdeka Curriculum to address learning loss involves character education through differentiated learning, optimization of the Project Penguatan Profil Pelajar Pancasila (P5) to strengthen students' national identity, and collaboration among the penta-helix (school principal, teachers, community, parents, and media). Effective communication by the school principal and their deputies with students' families was also critical in successfully implementing the Merdeka Currichool. This study highlights the importance of collaboration among the penta-helix in implementing the Merdeka Curriculum at schools.